EFEKTIVITAS PELAKSANAAN PROGRAM BERAS SEJAHTERA KAMPUNG SAPALEK DISTRIK NAPUA KABUPATEN JAYAWIJAYA - Irsan Yelipele; Musi Gwijange (Jurnal Ilmu Pemerintahan, 2025)
This study aims to determine the effectiveness of the implementation of the Prosperous Rice Program in Sapalek Village, Napua District, Jayawijaya Regency. This study used independent variables with the following indicators: Right on Target, Right on Quantity, Right on Quality, Right on Time, Right on Administration, and Right on Price. The author used random sampling for sampling, with a sample size of 20 families determined using the Slovin formula. Data analysis used descriptive quantitative analysis using scores. The results indicate that the effectiveness of the Prosperous Rice Program in Sapalek Village, Napua District, Jayawijaya Regency achieved a score of 53.1, which is considered quite good. This result was obtained from the indicators of Right on Target (51.3), Right on Quantity (45.3), Right on Price (51.3), Right on Time (56), Right on Quality (59.6), and Right on Administration (57.4).